THE PROBLEMS OF COASTAL AND MARINE RESOURCES MANAGEMENT IN INDONESIA - Supriharyono . (JOURNAL OF COASTAL DEVELOPMENT, 2000)
It is a well known fact that parts of the coastal marine ecosystem, such as estuaries, mangrove, sea-weed beds, and coral reefs, are very productive . The primary production may go up to 10,000 g C/m2vear in these systems. It t`s very high compared with the primary production in open seas that is only 50-100 g C/m2/year. As a result the rate of the secondary production, such as fish, and other marine faunas, which live in these system, are also high. Anthropogenic activities carried out in order to use the resources in coastal areas, such as destructive fishing practices, coral mining, mangrove cutting, may ayiectfish Hncluding other marine faunas) production. Considering the destructive nature of some human activities in the coastal areas, the Indonesian government has established several laws and regulations for marine environmental protection. These included the establishment of 37 marine conservation areas which cover an area of about 2,800,000 Ha. It is expected that these areas will be expanded to 30,000,000 Ha by the year 2000, but there is no assurance whether this expansion can be reached or not. In the meantime a strategt to [ind alternatives to destructive practices in coastal and marine ecosystems is being prepared.",